The Effect of the Smart Dasawisma Cadre Movement on Complete Basic Immunization Coverage among Infants: A Quasi-Experimental Study in Bangkalan - Eka Novianti, Besty; Anggraeni, Novi; M. Hasinuddin; Susanti, Eny (Universitas Muhammadiyah Sidoarjo, 2026)
Early marriage re Immunization is one of the most effective strategies for preventing disease transmission and reducing morbidity and mortality among infants and young children World Health Organization (WHO) data indicate that in 2023, global immunization coverage experienced stagnation, with several identified setbacks. This study aimed to analyze differences in immunization coverage before and after the implementation of the Smart Dasawisma kader Movement innovation. This innovation employed a quasi-experimental design using a one-group trial with a pre-test and post-test approach. The independent variable in this study was the smart dasawisma kader movement, while the dependent variable was the improvement in immunization complia. The study population consisted of 54 infants aged 9–12 months at the Kokop Community Health Center, selected using simple random sampling. The inclusion criterion was kader who were able to read and write. The Wilcoxon test results showed an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a statistically significant difference before and after the intervention These findings indicate a statistically significant difference in respondents’ immunization status before and after the intervention. Kader empowerment through structured mentoring is expected to be an effective strategy for improving immunization coverage.